2009
DOI: 10.1038/ki.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hepcidin levels are elevated but responsive to erythropoietin therapy in renal disease

Abstract: Hepcidin is a critical inhibitor of iron export from macrophages, enterocytes, and hepatocytes. Given that it is filtered and degraded by the kidney, its elevated levels in renal failure have been suggested to play a role in the disordered iron metabolism of uremia, including erythropoietin resistance. Here, we used a novel radioimmunoassay for hepcidin-25, the active form of the hormone, to measure its levels in renal disease. There was a significant diurnal variation of hepcidin and a strong correlation to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

46
266
8
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(335 citation statements)
references
References 32 publications
46
266
8
10
Order By: Relevance
“…As shown by Swinkels et al (11), there was almost 10-fold difference between lower limit of detection in SELDI (in study by Swinkels et al [11]) and immunodot (study by Nemeth et al [4]) in urinary hepcidin. The same difference was found between the assay by Ganz et al (12) and the assay by Ashby et al (13). In the studies by Ganz et al (12) and Zaritsky et al (14) reported in this issue of CJASN (using the same ELISA), the difference between detection limit was 10-fold, with 0.5 ng/ml in the study by Ashby et al (13) and 5 ng/ml in the assay developed by Ganz et al (12).…”
supporting
confidence: 59%
See 2 more Smart Citations
“…As shown by Swinkels et al (11), there was almost 10-fold difference between lower limit of detection in SELDI (in study by Swinkels et al [11]) and immunodot (study by Nemeth et al [4]) in urinary hepcidin. The same difference was found between the assay by Ganz et al (12) and the assay by Ashby et al (13). In the studies by Ganz et al (12) and Zaritsky et al (14) reported in this issue of CJASN (using the same ELISA), the difference between detection limit was 10-fold, with 0.5 ng/ml in the study by Ashby et al (13) and 5 ng/ml in the assay developed by Ganz et al (12).…”
supporting
confidence: 59%
“…The same difference was found between the assay by Ganz et al (12) and the assay by Ashby et al (13). In the studies by Ganz et al (12) and Zaritsky et al (14) reported in this issue of CJASN (using the same ELISA), the difference between detection limit was 10-fold, with 0.5 ng/ml in the study by Ashby et al (13) and 5 ng/ml in the assay developed by Ganz et al (12). Values of hepcidin in both studies varied the normal range for healthy volunteers was 2 to 55 ng/ml (fifth through 95th percentiles) versus 29 to 254 ng/ml for male patients and 18 to 288 ng/ml for female patients.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Of note, the CHD population investigated in our last study [24] was enrolled in a center characterized by a clinical policy favoring relatively low iron supplementation to avoid iron toxicity. Indeed, the median ferritin level in this CHD population was " only " 265 μ g/L (interquartile range 155 -411 μ g/L), while, e.g., in the previous study by Ashby and colleagues [15] the mean ferritin level in 94 CHD patients was 550 μ g/L (95% CI 291 and 1014 μ g/L, respectively). Moreover, again in the effort to select the most appropriate controls, we included only control subjects with biochemically documented normal iron status.…”
Section: Hepcidin As a Player In The Anemia Of Chdmentioning
confidence: 99%
“…It has therefore been hypothesized that in CHD patients increased hepcidin could aggravate functional iron deficiency by decreasing macrophage iron release and intestinal iron absorption, paving the way to the possible utilization of anti-hepcidin drugs for optimizing the management of anemia [9,21]. In regards to this point, it is of interest to note that administration of erythropoiesis stimulating agents (ESAs), by itself, has been reported to reduce hepcidin in patients with chronic kidney disease [15,22]. This is likely due to hypoxia-inducible factor via Epo-induced erythropoiesis [23], and suggests that the beneficial effect of Epo in CHD may be partly mediated by normalization of iron delivery.…”
Section: Hepcidin As a Player In The Anemia Of Chdmentioning
confidence: 99%